2007
DOI: 10.1159/000100394
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Increased Serum sFas Levels and Microalbuminuria in Type 1 Diabetic Patients

Abstract: Objective: The aim of this study was to elucidate if apoptosis dysregulation is present in type 1 diabetic patients with microalbuminuria. Subjects and Methods: The following variables were determined in 29 type 1 diabetic patients: the duration of diabetes, soluble Fas (sFas), Bcl-2, hemoglobin A1c levels, glomerular filtration rate (GFR) and microalbuminuria, using the urine albumin to urine creatinine ratio (ACR). Age and gender were assessed and patients were categorized into two groups, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Several genes in the donor region are functional candidates known to influence renal function and UAE including FAS (Tnfrsf6) (17) and discoidin domain receptor tyrosine kinase 1 (Ddr1) (5,8). Studies with recombinant congenics will be needed to reduce the number of positional candidates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genes in the donor region are functional candidates known to influence renal function and UAE including FAS (Tnfrsf6) (17) and discoidin domain receptor tyrosine kinase 1 (Ddr1) (5,8). Studies with recombinant congenics will be needed to reduce the number of positional candidates.…”
Section: Discussionmentioning
confidence: 99%
“…QTL analyses were performed using the R/qtl package from the R: Language and Environment program in 248 ZK.BN-Chr1 congenic F2 males (2,17). The genetic map for rat chromosome 1 was developed by first computing recombination frequencies between all markers using the est.rf function, then the construction of a genetic map was performed with the est.map function.…”
Section: Qtl Analysismentioning
confidence: 99%
“…S7). More importantly, soluble BCL2 protein has been detected in serum in a variety of disorders [51][55] and cerebrospinal fluid in traumatic brain injury [56], [57]. Notably, in children following head trauma increased levels of soluble BCL2 protein in spinal fluid correlated with improved survival [57].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed increased sFas values in subjects with type 2 DM, with signifi cantly higher levels in subjects with longer duration of diabetes [16]. Protopsaltis et al have observed positive correlation of sFas with microalbuminuria [17] and diabetic nephropathy [18][19][20]. Higher values of serum sFas have been found in patients in the advanced stage of renal disease as compared to the early stages [20].…”
Section: Discussionmentioning
confidence: 99%